Early Child Development: From Measurement to Optimal Functioning and Evidence-based Policy - Schiariti, Verónica (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In the early years of life, the environments that interact with a child-including families, schools, and communities-play a key role in the child's brain development. Early child development and overall children's developmental trajectories have long-term implications for health, happiness, and earning potential as these children become adults. Importantly, failing to reach developmental potential contributes to global cycles of poverty, inequality, and social exclusion. There is little public understanding of the importance of a child's first years and the critical developmental opportunity to reach optimal functioning. As such, global data on early child developments are crucial to inform the public and demand evidence-based policies and high-quality programs for children around the world. This book includes initiatives assessing the impact of programs and interventions related to children's health, education, and participation that inform evidence-based policies worldwide. Importantly, this book raises global awareness of the importance of children's first years of life and the crucial role of child-environment interactions where the child lives, plays, and grows. The culturally diverse content comprises international representation of studies and classifications tools. International experts contributed high-quality reviews that collate valuable information and guide the adoption of a rights-based approach in early child development globally.